Potentially inappropriate medications in older adults: a population-based cohort study. (11th October 2019) - Roux, Barbara; Sirois, Caroline; Simard, Marc; Gagnon, Marie-Eve; Laroche, Marie-Laure
Abstract: Background: Non-optimal medication use among older adults is a public health concern. A concrete picture of potentially inappropriate medication (PIM) use is imperative to ensure optimal medication use. Objective: To assess the prevalence of PIMs in community-dwelling older adults and identify associated factors. Methods: A retrospective population-based cohort study was conducted using the Quebec Integrated Chronic Disease Surveillance System (QICDSS). The QICDSS includes data on drug claims for community-dwelling older adults with chronic diseases or at risk of developing chronic diseases aged ≥65 years who are insured by the public drug insurance plan. Individuals aged ≥66 years who were continuously insured with the public drug plan between 1 April 2014 and 31 March 2016 were included. PIMs were defined using the 2015 Beers criteria. We conducted multivariate robust Poisson regression analyses to explore factors associated with PIM use. Results: A total of 1 105 295 individuals were included. Of these, 48.3% were prescribed at least one PIM. The most prevalent PIMs were benzodiazepines (25.7%), proton-pump inhibitors (21.3%), antipsychotics (5.6%), antidepressants (5.0%) and long-duration sulfonylureas (3.3%). Factors associated with PIM exposure included being a woman [rate ratio (RR): 1.20; 95% confidence interval (CI): 1.20–1.21], increased number of medications and having a high number of chronic diseases, especially mental disorders (RR: 1.50; 95% CI: 1.49–1.51). Conclusion: Almost one out of two community-dwelling older adults use a PIM. It is imperative to reduce the use of PIMs, by limiting their prescription and by promoting their deprescribing, which necessitates not only the active involvement of prescribers but also patients.